Improving fashion design learning outcomes by problem based learning model in Vocational High School - Ernawati, Ernawati; Ferdian, Feri; Zur, Rohana (Universitas Negeri Padang, 2023)
The background of this research problem was the low learning outcomes of students in the cognitive domain of Fashion Design course. This research aims at describing the implementation of the Problem Based Learning model to improve student learning outcomes in the Fashion Design course. The research was conducted at Vocational High School 6 Padang with the method used was Classroom Action Research (CAR). This Classroom Action Research (CAR) was divided into 2 cycles. Each cycle was divided into 4 stages: 1) Planning, 2) Implementation. 3) Observation, 4) Reflection. The research subjects used were students of Grade XI Fashion Design I at Vocational High School 6 Padang, totaling 29 students. Data collection techniques used observation, tests, and documentation. The data analysis technique was carried out by quantitative and qualitative analyzing. In the first cycle, students reached the Minimum Completeness Criteria of learning outcomes as much as 55%. In the second cycle, it increased while 83% of students have reached the Minimum Completeness Criteria. Thus, it can be concluded that the implementation of Fashion Design learning by using the Problem Based Learning Model can improve student learning outcomes in grade XI Fashion Design I at Vocational High School 6 Padang.